2022
DOI: 10.53332/kmj.v10i3.668
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative therapies for premenstrual syndrome: an exploratory study

Abstract: Background: Data related to the use of complementary and alternative therapies (CAT) forpremenstrual syndrome in the communities is scarce. There is very limited information aboutcomplementary and alternative therapies practice among nursing students in Dakhalia governorate,Egypt.Methods: A descriptive exploratory design was conducted in Dakahlia governorate, Egypt, on all secondary technical nursing schools students to explore the use of complementary and alternative therapies to relieve premenstrual syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…9 Essential oils (EOs) have been used in complementary and alternative medicine (CAM) for the prevention and treatment of diseases. 10 Aromatherapy is a component of CAM, which involves the inhalation of EOs, some of them used to counteract gynecological ailments. 2 In fact, literature confirmed that EOs relief multiple symptoms of PMS.…”
Section: Introductionmentioning
confidence: 99%
“…9 Essential oils (EOs) have been used in complementary and alternative medicine (CAM) for the prevention and treatment of diseases. 10 Aromatherapy is a component of CAM, which involves the inhalation of EOs, some of them used to counteract gynecological ailments. 2 In fact, literature confirmed that EOs relief multiple symptoms of PMS.…”
Section: Introductionmentioning
confidence: 99%